2009
DOI: 10.1128/jvi.01805-08
|View full text |Cite
|
Sign up to set email alerts
|

Novel Influenza Virus NS1 Antagonists Block Replication and Restore Innate Immune Function

Abstract: The innate immune system guards against virus infection through a variety of mechanisms including mobilization of the host interferon system, which attacks viral products mainly at a posttranscriptional level. The influenza virus NS1 protein is a multifunctional facilitator of virus replication, one of whose actions is to antagonize the interferon response. Since NS1 is required for efficient virus replication, it was reasoned that chemical inhibitors of this protein could be used to further understand virus-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 69 publications
0
98
1
1
Order By: Relevance
“…A recent study showed that several chemicals ( Figure 1) that can bind to NS1A and inhibit the virus replication, but the binding region of these chemicals were not determined [13]. In 2011, they found a new inhibitor JJ3297 which has a similar structural scaffold with NSC125044 can block multi-cycle replication in an RnaseL-dependent manner and also can not determine the bind region [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that several chemicals ( Figure 1) that can bind to NS1A and inhibit the virus replication, but the binding region of these chemicals were not determined [13]. In 2011, they found a new inhibitor JJ3297 which has a similar structural scaffold with NSC125044 can block multi-cycle replication in an RnaseL-dependent manner and also can not determine the bind region [14].…”
Section: Introductionmentioning
confidence: 99%
“…Just recently a yeast-based assay has been developed to identify chemical inhibitors that phenotypically suppress NS1 functions, most likely by inhibiting NS1 interactions with other proteins (Basu et al , 2009 ). In this screen several inhibitors have been identifi ed that exhibited a specifi c activity against infl uenza virus but not against respiratory syncicial virus (e.g., JJ 3297).…”
Section: Approaches To Disrupt Virus-host Cell or Protein Interactionsmentioning
confidence: 99%
“…In this screen several inhibitors have been identifi ed that exhibited a specifi c activity against infl uenza virus but not against respiratory syncicial virus (e.g., JJ 3297). Interestingly, viruses were resistant against these compounds in interferon defi cient systems, indicating that the agents act via disruption of the interferon antagonistic activity of NS1 (Basu et al , 2009 ;Walkiewicz et al , 2011 ). Another screening approach has been developed to search for compounds that disrupt interaction of the NS1 protein with RNA, based on the rationale that some functions of NS1 are executed by the ability of the protein to bind various types of RNA molecules from both viral and non-viral origin (Maroto et al , 2008 ).…”
Section: Approaches To Disrupt Virus-host Cell or Protein Interactionsmentioning
confidence: 99%
“…Particularly, antimicrobial peptides can exert a broad spectrum of activity on infectious agents; they can be highly specific and effective and even biodegraded by peptidases, which limit their accumulation and results in lower toxicity (GALDIERO et al, 2013). Several reports have shown the antiviral potential of synthetic and naturally occurring peptides against different viruses such as HHV-1 and HHV-2, human immunodeficiency virus (HIV), vesicular stomatitis virus (VSV), influenza A virus, cytomegalovirus, adenovirus, rotavirus and other viruses (DAHER et al, 1986;CARRIEL-GOMES et al, 2007;BASU et al, 2009). The objective of this study was to investigate the antiviral potential and the in vitro mechanism of action of the antimicrobial peptide P34 against bovine alphaherpesvirus type 1 (BoHV1).…”
Section: Introductionmentioning
confidence: 99%